Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Mutu Pendidikan - Muarif Mahmud Suhada (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
Transformation is essentially turning potential into real energy. Madrasah principals who are able to carry out leadership transformations mean that they can turn the potential of their institutions into energy to improve the quality of educational processes and outputs. This study aims to describe and analyze the transformational leadership of the Madrasah Principal at MI Muhammadiyah Madureso. This research is a qualitative descriptive study by taking MI Muhammadiyah Madreso. Data collection techniques used observation, documentation and interviews, data validity used triangulation techniques, and data analysis was carried out by data collection, data reduction, and drawing conclusions. The results of the study show: (1) The leadership of the head of MI Muhammadiyah Madureso Kuwarasan Kebumen has and implements Idealized Influence. The behavior of the madrasah head can be used as an example for madrasah residents so that it creates respect, and in his daily life can provide motivation and self-confidence to his subordinates. The principal of the madrasah is also able to give empathy to his subordinates. (2) Head of MI Muhammadiyah Madureso Kuwarasan Kebumen owns and implements Inspirational Motivation. The behavior of the madrasa head is able to motivate and inspire his subordinates to continue to develop themselves for the advancement of education. The head of the madrasa always gives new job challenges and is a pioneer of good for the madrasa residents. (3) Head of MI Muhammadiyah Madureso Kuwarasan Kebumen owns and implements Intellectual Stimulation. The behavior of the madrasa head is based on knowledge that is able to carry out innovations to improve the quality of madrasas. The principal of the madrasa always follows changes by behaving productively, being able to explore creative ideas and solutions from his subordinates. (4) Head of MI Muhammadiyah Madureso Kuwarasan Kebumen owns and implements Individual Consideration. The madrasa head always identifies the needs and recognizes the abilities of his subordinates, inspires learning enthusiasm and provides opportunities to develop his abilities, also always listens to subordinates' complaints and delegates some of the tasks and authority to his subordinates.